2021
DOI: 10.1136/tsaco-2020-000655
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study of US trauma centers examining the effect of the COVID-19 pandemic on injury causes, diagnoses and procedures

Abstract: BackgroundThe COVID-19 pandemic resulted in nationwide social distancing and shelter-in-place orders meant to curb transmission of the SARS-CoV-2 virus. The effect of the pandemic on injury patterns has not been well described in the USA. The study objective is to determine the effect of the COVID-19 pandemic on the distribution and determinants of traumatic injuries.MethodsThis retrospective multi-institutional cohort study included all hospital admissions for acute traumatic injury at six community level I t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 34 publications
3
50
1
Order By: Relevance
“…Number of RTC presentation reduced by 48% [ 60 ] USA Les Angeles County trauma center − 2 NA Trauma decreased with fewer motor vehicle collisions [ 128 ] Multicenter study of US trauma centers − 11 − 27 Overall, trauma admission was reduced by 11%. There was a decrease in number of RTC admission by 27% [ 129 ] UC Davis Medical Center NA − 38 38% reduction in motor-vehicle injury [ 47 ] McLaren Oakland Hospital (MOH) in Pontiac, MI − 45 *2020 versus March–April 2016–2019 − 46 Overall, trauma admission reduced by 45%. There was a decrease in RTC admission by − 46% [ 107 ] Portsmouth Regional Hospital − 57 *February–April 2020 versus 2017–2019 − 81 *February–April 2020 versus 2017–2019 Overall, trauma admission was reduced by − 57%.…”
Section: Resultsmentioning
confidence: 99%
“…Number of RTC presentation reduced by 48% [ 60 ] USA Les Angeles County trauma center − 2 NA Trauma decreased with fewer motor vehicle collisions [ 128 ] Multicenter study of US trauma centers − 11 − 27 Overall, trauma admission was reduced by 11%. There was a decrease in number of RTC admission by 27% [ 129 ] UC Davis Medical Center NA − 38 38% reduction in motor-vehicle injury [ 47 ] McLaren Oakland Hospital (MOH) in Pontiac, MI − 45 *2020 versus March–April 2016–2019 − 46 Overall, trauma admission reduced by 45%. There was a decrease in RTC admission by − 46% [ 107 ] Portsmouth Regional Hospital − 57 *February–April 2020 versus 2017–2019 − 81 *February–April 2020 versus 2017–2019 Overall, trauma admission was reduced by − 57%.…”
Section: Resultsmentioning
confidence: 99%
“…The reported reduction of the incidence of RTCs varied in different studies. Although some studies reported a reduction in the incidence [12][13][14], others found that it did not change [15][16]. Similarly, the incidence of bicycle injuries in other studies varied depending on whether the use of bicycles was encouraged as the preferred mode of exercise/transport during the Pandemic [14,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Wähnert et al [ 13 ], the changes of trauma patient numbers were most pronounced in smaller trauma centres, whereas level I trauma centres even observed a slight increase of emergency cases. Furthermore, for some causes of accidents (assaults, self-inflicted injuries, and injuries associated with home improvement projects), no significant changes or even an increased incidence was described [ 14 ]. The authors of the aforementioned studies uniformly concluded that, although the number of trauma patients decreased in the exceptional state of the pandemic, there is still a significant need for functioning structures for the care of trauma patients, as their numbers still remains high.…”
Section: Discussionmentioning
confidence: 99%